Reply to Comment on 'A new simpler way to obtain high fusion power gain in tandem mirrors'. (6th November 2017) - Fowler, T.K.; Moir, R.W.; Simonen, T.C.
Abstract: Our response is to call attention to the possibility of utilizing pulsed ECH to stabilize trapped particle modes.